Dermatitis Atopic with Secondary Infection - Nanda, Kharisma Sukma; Putri, Adelita VegaDwi; Niari, Tapi Singgar; Rahmawati, Yuli Wahyu (MAGNA MEDICA Berkala Ilmiah Kedokteran dan Kesehatan, 2022)
Background: Atopic dermatitis is a chronic and residive skin inflammation, which is often found in patients with allergic rhinitis and asthma and among their family members, which is characterized by skin disorders in the form of itchy papules, which then undergo excoriation and lichenification, distribution in body folds. At the age of 4-16 years, the predilection for dermatitis is found on the upper body and face, generally symmetrical dermatitis appears in the flexure area, hands, and feet.Case Presentation: The following is a case report of a 16-year-old male patient as a student. The patient was diagnosed with atopic dermatitis with complaints of itching in the neck area, hand folds, and leg folds. Initially itchy, filled with clear fluid in the neck then spread to the folds of the hands and feet. Itchy, hot, and painful when sweating. Lesions ad Regio colli, superior and inferior extremities show lichenified lesions with irregular shape, poorly demarcated with bilateral spread, accompanied by squama and excoriations.Conclusion: Atopic dermatitis is a chronic inflammation of the skin, which may manifest as itchy papules that become excoriated and lichenified. Predilection can be determined based on the age of the patient.